The level of linguistic intelligence among female kindergarten students at Tishreen University (A field study in the city of latakia) - حاتم عبير (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the research is to identify the level of linguistic intelligence among female kindergarten students at Tishreen University according to the four years of study. To achieve the objective of the research, the researcher developed a measure of linguistic intelligence, and it was confirmed that its validity and reliability were then applied to a sample of (194) female kindergarten students at Tishreen University. The results showed that: the level of linguistic intelligence among female kindergarten students is average, and it also showed that there were no statistically significant differences in the total score for the level of linguistic intelligence among female kindergarten students at Tishreen University according to the years of study. And in light of the research results, the research presented several suggestions.